Biochemical characterization of PER-2 and genetic environment of bla PER-2 - Power, Pablo (2007)
PER-2 was the first detected and the second most prevalent extended-spectrum β-lactamase in clinical pathogens isolated in Argentina and was also reported only in other South American countries. Citrobacter freundii 33587 was isolated in 1999 in Buenos Aires and was resistant to all tested β-lactams except cephamycins and carbapenems. The strain produced both plasmid-borne TEM-1 and PER-2 (pI 5.4), which could be transferred by conjugation. By PCR screening, thermal asymmetric interlaced PCR, and DNA sequencing, we detected an ISPa12/IS1387a insertion sequence upstream of blaPER-2, previously reported as also being associated with bla PER-1. The presence of similar structures upstream of bla PER-1 and blaPER-2 suggests a common origin and mobilization. Compared to blaPER-1 genes, an additional putative promoter for blaPER-2 was found. PER-2 kinetic analysis showed its high hydrolysis efficiencies toward both CTX and CAZ (kcat/K m, 0.76 and 0.43 μM-1·s-1, respectively).